26.6: Spectroscopic Response of Polymer Network Liquid Crystal Cell. (4th October 2019) - Tang, Shu Tuen; Meng, Cuiling; Tseng, Man Chun; Kwok, Hoi Sing
Abstract : The Polymer Network Liquid Crystal (PNLC) cell we fabricated is operating in a reverse mode of voltage‐off transparent state. It is found that when we apply voltage to the PNLC cells, the transmitted light color changed gradually and finally became a bit blue. This effect is not found in Polymer Dispersed LC (PDLC) window. The wavelength dependent transmittance voltage curves are reported and we will try to explain this effect by applying the anomalous diffraction theory.